2010
DOI: 10.1038/ijir.2009.61
|View full text |Cite
|
Sign up to set email alerts
|

The relation between sexual interest and personality characteristics in men: an eye-tracking study

Abstract: There is a large individual deviation for men, which may be caused by a difference in personality characteristics, in sexual interest in response to sexual stimuli. In this study, we investigate whether attention to the sexual region in a video depends on the personality characteristics of men, assessing this with an eye-tracking system. The study included 30 healthy males with a normal psychological state, who viewed a sexual video in which the sexual region had been designated. Visual attention was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“… 17 We previously reported that even the normal variation of personality characteristics is associated with sexual interest in men by using the specified questionnaire used in personality tests worldwide. 12 Thus, the degree of masculinity in our subjects might have affected our results. We suggest that this is only a pilot study that should be repeated with a larger sample and more accurate methodology.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“… 17 We previously reported that even the normal variation of personality characteristics is associated with sexual interest in men by using the specified questionnaire used in personality tests worldwide. 12 Thus, the degree of masculinity in our subjects might have affected our results. We suggest that this is only a pilot study that should be repeated with a larger sample and more accurate methodology.…”
Section: Discussionmentioning
confidence: 93%
“…Our methodology was published previously. 11 , 12 Briefly, the participants viewed audiovisual material in the form of three different sexually explicit video clips.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, clearer articulation of the interrelationships between mental health distress, SEMB, and risky sexual health perceptions and behaviors is needed. Given that reciprocal relationships are probable, future research explicating these possibilities will require more extensive research designs (e.g., longitudinal studies); inclusion of more extensive environmental (e.g., social support) [24,84,85] and personal (e.g., individual differences) determinants [86–88]; and more sophisticated analytical strategies (e.g., multilevel models, structural equation models). Nevertheless, the findings suggest that evidence‐based sexual health promotion strategies simultaneously addressing individuals' SEMB and their mental health needs might be a useful approach to improve mental health and address preventable sexual health outcomes associated with SEMB.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated whether attention to the sexual region in the video depends on the personality characteristics of men, assessing this with an eye-tracking system. Regarding the gaze duration for the sexual region, multiple stepwise regression analysis showed that only social introversion was associated negatively 13) . It was unclear whether these differences were a result of a congenital or an acquired factor.…”
Section: Analysis Of Sexual Interestmentioning
confidence: 99%